2011
DOI: 10.1293/tox.24.163
|View full text |Cite
|
Sign up to set email alerts
|

GABA and Dopamine Release from Different Brain Regions in Mice with Chronic Exposure to Organophosphate Methamidophos

Abstract: Organophosphates such as methamidophos, usually used in the agricultural field, have harmful effects on humans. Exposures to insecticides has been associated with many disorders, including damage to the central and peripheral nervous system. Chronic exposure to organophosphates may lead to persistent neurological and neurobehavioral effects. This study was conducted to determine the effect of methamidophos on [3H]-dopamine (DA) and gamma aminobutyric acid (GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[79], 2.6 mg/kg of methamidophos was administered to male BALB/c mice every three days, until the mice were three, six or nine months old. Exposure to methamidophos was related to a decrease of GABA release in the cerebral cortex after three months, while an increase of GABA release in the same brain area was observed after nine months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[79], 2.6 mg/kg of methamidophos was administered to male BALB/c mice every three days, until the mice were three, six or nine months old. Exposure to methamidophos was related to a decrease of GABA release in the cerebral cortex after three months, while an increase of GABA release in the same brain area was observed after nine months.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, decreased GABA levels were observed after exposure of adult male Lister hooded rats to a single dose of 250 mg/kg of the organophosphate chlorpyrifos Furthermore, in a study by Noriega-Ortega et al . [79] male BALB/c mice were exposed to 2.6 mg/kg of methamidophos every three days resulting in a decrease of GABA release in the cortex and hippocampus after three and six months. An exposure to 30 mg/kg/day of the phthalate DEHP throughout gestation until weaning (GD1-PND21) also resulted in decreased GABA levels in prepubertal male rats.…”
Section: Resultsmentioning
confidence: 99%
“…They indicated that this widely used OP pesticide is deleterious to brain function. Noriega‐Ortega et al () reported that MT, like other OP, disrupts endocrine pathways and the results indicate changes in gamma aminobutyric acid and dopamine neurotransmission, suggesting a specific neuronal damage. Moreover, MT induced diaphragm muscle necrosis and brain oxidative stress (Kalkan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sustková-Fišerová et al (2009) showed that socially isolated non-aggressive mice had almost three times higher levels of GABA in the pre-frontal cortex when compared with aggressive mice. Additionally, chronic exposure to methamidophos was shown to decrease GABA release in cerebral cortex and hippocampal slices (Noriega-Ortega et al 2011). …”
Section: Discussionmentioning
confidence: 99%